The Efficacy of Persian Medicine Based Life Style Modification on Functional Bloating: A Randomized Controlled Clinical Trial - Alireza Moulazadeh (Traditional and Integrative Medicine, 2021)
Functional bloating is one of the gastrointestinal diseases that impacts the quality of life and social activities of the patients. The present study aimed to evaluate the effectiveness of lifestyle modification based on Persian Medicine (PM) on functional bloating improvement. Fifty patients with functional bloating and ROME III confirmation criteria were enrolled in the study groups of control and intervention. The intervention group received lifestyle modification education based on PM perspectives, and the control group did not receive any training. The score of implementing PM recommendations by patients was evaluated by the questionnaire of “compliance with the PM principles effective on functional bloating” once every two weeks during the two months of the study. The severity of clinical Complications Associated with Functional Bloating (CAFB) was also evaluated before and after the study by visual analog scale. Primary and secondary outcomes were analyzed by t-test and ANCOVA in SPSS version 19. The qualitative data analysis was performed via Chi-square and Mann-Whitney tests. The severity of clinical CAFB was significantly higher in women at baseline (P = 0.027). Lifestyle modification of patients led to a gradual increase in compliance with the PM principles. By the end of the study, the mean score of compliance with the PM principles in the intervention group was significantly higher compared to the pre-intervention score (P<0.0001) and also compared to the control group (P < 0.0001). Besides, the educational intervention resulted in a significant decrease (51.8%) in the mean severity of all clinical CAFB in the intervention group before and after training (P < 0.0001) and between the control group and the intervention group (P < 0.0001). Therefore, Lifestyle modification based on PM probably can be effective in improving the clinical complications of functional bloating.